Adopsi Nilai dan Prinsip Hukum Pidana Islam tentang Delik Kesusilaan Zina dalam Kitab Undang-undang Hukum Pidana Nasional - Mahrus Ali; Muhammad Abdul Kholiq (Fakultas Hukum Universitas Islam Indonesia, 2023)
This research focuses on the fundamental justification for the policy of inserting Islamic criminal law values into the National Criminal Code, especially regarding the policy of criminalizing the moral offense of adultery and the form of adoption of the said values and principles of Islamic criminal law in the National Criminal Code, particularly on the policy of criminalizing the moral offense of adultery. This is a normative legal research with statutory, philosophical and policy approaches. This research concludes that theoretically (socio-historically based) and juridically (based on the values of the Pancasila philosophy, mainly the first principle and the 1945 Constitution, specifically article 29), the absorption of Islamic criminal law values in the preparation of the Criminal Code is a historical and constitutional right. Values and the principles of Islamic criminal law regarding the moral offense of adultery have not been fully absorbed in the National Criminal Code. Some forms of adoption that have reflected the values and principles of Islamic criminal law are the expansion of the scope of acts criminalized as adultery, the philosophy of prohibiting adultery and the threat of criminal sanctions against adultery. Some Acts that are essentially moral offenses of adultery but are not criminalized as moral offenses of adultery, i.e. rape, prostitution and enjoying pornographic content for oneself.Keyword: Adoption; Values and Principles of Islamic Criminal Law; Moral Offenses of Adultery and the Criminal Code AbstrakPenelitian ini berfokus pada dasar justifikasi kebijakan mengadopsi nilai-nilai hukum pidana Islam dalam KUHP Nasional khususnya mengenai kebijakan kriminalisasi delik kesusilaan zina dan bentuk adopsi terhadap nilai-nilai dan prinsip-prinsip hukum pidana Islam dalam KUHP Nasional khususnya mengenai kebijakan kriminalisasi delik kesusilaan zina. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan, filsafat dan kebijakan. Penelitian ini menyimpulkan bahwa secara teoritis (berbasis sosio-historis) dan secara yuridis (berbasis nilai falsafah Pancasila khususnya sila pertama dan UUD 1945 khususnya Pasal 29, penyerapan nilai-nilai hukum pidana Islam dalam penyusunan KUHP adalah suatu hak sejarah dan hak konstitusional. Nilai dan prinsip hukum pidana Islam tentang delik kesusilaan zina belum sepenuhnya terserap dalam KUHP Nasional. Beberapa bentuk adopsi yang sudah mencerminkan nilai dan prinsip hukum pidana Islam ialah mengenai adanya perluasan cakupan tentang perbuatan yang dikriminalkan sebagai zina, filosofi pelarangan zina dan ancaman sanksi pidana terhada zina. Beberapa perbuatan yang hakikatnya merupakan delik kesusilaan zina tetapi tidak dikriminalisasi sebagai delik kesusilaan zina yaitu perkosaan, pelacuran dan menikmati untuk diri sendiri terhadap konten pornografi.Kata Kunci: Adopsi; Delik Kesusilaan Zina dan KUHP; Nilai dan Prinsip Hukum Pidana Islam.